2013
DOI: 10.1038/ni.2566
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of inflammation and acute lung injury by Miz1 via repression of C/EBP-δ

Abstract: Inflammation is essential for host defense but can cause tissue damage and organ failure if unchecked. How the inflammation is resolved remains elusive. Here we report that the transcription factor Miz1 was required for terminating lipopolysaccharide (LPS)-induced inflammation. Genetic disruption of the Miz1 POZ domain, which is essential for its transactivation or repression activity, resulted in hyper-inflammation, lung injury and increased mortality in LPS-treated mice while reduced bacterial load and morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 49 publications
6
75
0
Order By: Relevance
“…Accordingly, BCL6-deficient macrophages were hypersensitive to LPS. Similarly, deletion of the BTB domain from the Myc-interacting zinc finger protein 1 (MIZ1) (encoded by the Zbtb17 gene), induced a hyperinflammatory response to LPS (23). In this instance, phosphorylation of MIZ1 enabled the protein to recruit HDAC1 to establish a repressive transcriptional complex.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, BCL6-deficient macrophages were hypersensitive to LPS. Similarly, deletion of the BTB domain from the Myc-interacting zinc finger protein 1 (MIZ1) (encoded by the Zbtb17 gene), induced a hyperinflammatory response to LPS (23). In this instance, phosphorylation of MIZ1 enabled the protein to recruit HDAC1 to establish a repressive transcriptional complex.…”
Section: Discussionmentioning
confidence: 99%
“…The negative effects of alcohol consumption have been linked to an increased inflammatory response, including increased cytokine release (14,15,37,38). Pro-inflammatory cytokines such as IL-1β, TNF, IL-6 and IL-8 have been identified as important contributors to the pathogenesis of organ damage, including lung as well as liver injury in models of acute inflammation (17)(18)(19)(39)(40)(41)(42). Together with IL-6, IL-8 binds to molecules that are involved in neutrophil activation, trafficking and infiltration of tissues in models of acute lung and liver injury (18,43).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-127 renders mice more susceptible to endotoxin-induced lung injury and sepsis Next, we assessed the in vivo function of miR-127 using a murine model of lung inflammation and injury induced by LPS (26). The data showed that, compared with the control animals, the mice pretreated with miR-127 exhibited more severe alveolar damage, as evidenced by the increased interstitial edema and debris deposit in the air space (Fig.…”
Section: Mir-127 Promotes M1 Signature Gene Expression While Repressimentioning
confidence: 98%